Diurnal Variation and Spatial Distribution Effects on Sulfur Speciation in Aerosol Samples as Assessed by X-Ray Absorption Near-Edge Structure (XANES) - Siwatt Pongpiachan; Kanjana Thumanu; Warangkana Na Pattalung; Phoosak Hirunyatrakul; Itthipon Kittikoon; Kin Fai Ho; Junji Cao (Journal of Analytical Methods in Chemistry)
This paper focuses on providing new results relating to the impacts of Diurnal variation, Vertical distribution, and Emission source on sulfur K-edge XANES spectrum of aerosol samples. All aerosol samples used in the diurnal variation experiment were preserved using anoxic preservation stainless cylinders (APSCs) and pressure-controlled glove boxes (PCGBs), which were specially designed to prevent oxidation of the sulfur states in PM10. Further investigation of sulfur K-edge XANES spectra revealed that PM10 samples were dominated by S(VI), even when preserved in anoxic conditions. The “Emission source effect” on the sulfur oxidation state of PM10 was examined by comparing sulfur K-edge XANES spectra collected from various emission sources in southern Thailand, while “Vertical distribution effects” on the sulfur oxidation state of PM10 were made with samples collected from three different altitudes from rooftops of the highest buildings in three major cities in Thailand. The analytical results have demonstrated that neither “Emission source” nor “Vertical distribution” appreciably contribute to the characteristic fingerprint of sulfur K-edge XANES spectrum in PM10.